2011
DOI: 10.3366/shr.2011.0033
|View full text |Cite
|
Sign up to set email alerts
|

Cromwell's Edinburgh Press and the Development of Print Culture in Scotland

Abstract: Alasdair Mann, the noted scholar of book culture in early modern Scotland, has suggested that a significant change had occurred in Scotland's relationship with the printed word by the late seventeenth century. This study sets out to explain how the interregnum served as a ‘watershed’ during which a consumer demand was created for popular print and how this in turn necessitated a significant increase in the production and distribution of printed material. Beginning with the sale of the press and patent of Evan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The earl's nemesis, Oliver Cromwell, would have been pleased. Spurlock details Cromwell's role in shaping the printing industry in Scotland. Spurlock focuses on the sales of presses in Edinburgh.…”
Section: –1700mentioning
confidence: 99%
See 1 more Smart Citation
“…The earl's nemesis, Oliver Cromwell, would have been pleased. Spurlock details Cromwell's role in shaping the printing industry in Scotland. Spurlock focuses on the sales of presses in Edinburgh.…”
Section: –1700mentioning
confidence: 99%
“…Spurlock details Cromwell's role in shaping the printing industry in Scotland. Spurlock focuses on the sales of presses in Edinburgh. Apparently, the book trade expanded during a period of general economic decline.…”
Section: –1700mentioning
confidence: 99%
“…Perhaps most significantly, this article will argue against assumptions that Cromwellian justifications for the invasions of Ireland and Scotland were prompted and guided by 'regionally distinctive approaches,' 12 which assumptions imply that the invasion of Ireland was driven by an apocalyptic anti-Catholicism while the invasion of Scotland proceeded with a cautious and nuanced appreciation of its Reformed heritage. 13 In fact, an under-noticed strand of apocalyptic thinking in the Cromwellian justifications for the Scottish invasion illustrates the extent to which English military and religious leaders were prepared to use apocalyptic language to denounce Scottish Protestants.…”
mentioning
confidence: 99%
“…14 Charles, who had been secretly negotiating with the Covenanters during Montrose's campaign, continued his political manoeuvring, and agreed a draft of the Treaty of Breda while resisting pressure to subscribe to the covenants. These manoeuvrings were not necessarily understood by his enemies: English observers reported that the king 'behaves himself like an obedient Son of the Kirk, is very modest, and as silent as midnight; He never moves but like a Puppet, upon the wire of the Covenant, and ambles altogether after their 4 Interpretation.' 15 The Kirk party agitated for the expulsion of 'Malignants' from Charles' court, meanwhile, and succeeded in removing former Engagers from the army, with disastrous effects on morale.…”
mentioning
confidence: 99%
See 1 more Smart Citation